Pelatihan Guru MTS Arifah Gowa terkait Penerapan Keterampilan Proses dalam Pembelajaran - Bedduside, Nurhayati; Patongai, Dian Dwi Putri Ulan Sari; Suryani, A. Irma; Sahribulan, Sahribulan; Hadis, Abdul (PT Ininnawa Paramacitra Edu, 2024)
Scientific process skills are an essential abilities in education and daily life, including observation, experimentation, analysis and drawing conclusions to understand natural phenomena. This abilities is relevant not only in the academic field but also has a positive impact in various aspects of life. Scientific process skills develop critical and analytical thinking, helping students understand how to think scientifically, solve problems, and make decisions based on evidence. Additionally, these skills enhance curiosity and a passion for research, making students lifelong learners. In the era of technology and innovation, scientific process skills are an important basis for developing expertise in various industries. Integrating these skills in education forms academically competent individuals and prepares them to face global challenges and contribute to the development of society through critical scientific thinking and solutions. This training was carried out at MTS Arifah Gowa. The results of implementing this training show a significant impact on improving the quality of learning. Skills such as observation, experimentation, analysis, and drawing conclusions provide a strong foundation for understanding scientific concepts. The results of the training showed that all participating teachers were very enthusiastic, based on the results of the questionnaire/instrument filled out after the training. Teachers stated that this training was very useful and relevant for improving the quality of science learning in schools. Teachers feel more prepared and confident in integrating science process skills into their curriculum, which is expected to improve overall student learning outcomes..